Upper critical magnetic field of LnO0.5F0.5BiS2 (Ln = La, Nd) superconductors at ambient and high pressure. (25th September 2017) - Fang, Y; Wolowiec, C T; Breindel, A J; Yazici, D; Ho, P-C; Maple, M B
Abstract: The upper critical fields H c 2 of polycrystalline samples of Ln O 0.5 F 0.5 BiS2 ( Ln = La, Nd) at ambient pressure (tetragonal structure) and high pressure (HP) (monoclinic structure) have been investigated via electrical resistivity measurements at various magnetic fields up to 8.5 T. The H c 2 ( T ) curves for all the samples show an uncharacteristic concave upward curvature at temperatures below T c, which cannot be described by the conventional one-band Werthamer–Helfand–Hohenberg theory. For the LaO 0.5 F 0.5 BiS2 sample under HP, as temperature is decreased, the upper critical field H onset, estimated from the onset of the superconducting transitions, increases slowly between 4.9 and 5.8 T compared with the slope of H onset ( T ) below 4.9 T and above 5.8 T. This anomalous behavior reveals a remarkable similarity in superconductivity between LaO 0.5 F 0.5 BiS2 samples measured under HP and synthesized under HP, although the crystal structures of the two samples were reported to be different. A reasonable explanation is that local atomic environment, which can be tuned by applying external pressure, is essential to the enhancement of T c for BiS2 -based superconductors. On the other hand, such anomalous behavior is very subtle in the case of NdO 0.5 F 0.5 BiS2 under HP, suggesting that the anisotropy of the upper critical field in the ab -plane and the possible lattice deformation induced by external pressure is weak. This explains why the pressure-induced enhancement of T c for NdO 0.5 F 0.5 BiS2 is not as large as that for LaO 0.5 F 0.5 BiS2 .